Acceptability of the Kangaroo Mother Care at the University Hospital of Treichville in Côte d'Ivoire - Daouda Doukouré; Kadidiatou Raissa Kourouma; Marie Laurette Agbré Yacé; Lassina Cissé; Chantière Some Méazieu; Mathilde N'Guetta Manouan; Ester Annick Lasme; Syntyche Bayo; Sassor Odile Purifine Aké-Tano; Julie Sackou Kouakou; Virginie Konan Kouakou (AOSIS, 2022)
Background. Kangaroo Mother Care (KMC) is a low-tech, high-impact intervention for preterm and low-birth-weight newborns. In 2019, Côte d'Ivoire opened its first KMC unit. We wanted to determine KMC's acceptability in Côte d'Ivoire after a year. Methods.  This qualitative study used semi-structured interviews in September 2020 at the Teaching Hospital of Treichville's first KMC unit. Mothers of preterm and low birth weight babies who received KMC were studied. Deductive (TFA-driven) framework analysis was performed. Coded using Nvivo 12. Results. KMC was acceptable overall. Mothers knew KMC's goal and benefits, including self-confidence and breastfeeding benefits. Most women reported that the method was easy to implement and were confident in implementing KMC at the unit or in the household, even though some of them found KMC not aligned with their cultural values. Some mothers, especially housewives and self-employed, highlighted the benefits of KMC, but they must have given up. Conclusions. Our study highlighted the need to increase KMC awareness, advocacy, education, and training for pregnant women and the community to reduce preterm and low birth weight infant mortality and morbidity.